"Irenaean" or "Schleiermacherian"?: An Evolutionarily Plausible Account of the Origins of Sin. Issue 2 (2nd April 2016) - Pedersen, Daniel
ABSTRACT: In this essay I argue that Irenaeus of Lyons' account of sin and the Fall is mistakenly championed. In the first place, Irenaeus' actual account does not fit the description of what many call "Irenaean". In the second place, Irenaeus' actual account of sin and the Fall is no more adequate to the problems posed by modern evolution than Augustine's. However, all is not lost, for, while an "Irenaean" account bears little resemblance to Irenaeus of Lyons' account, it is remarkably similar to Friedrich Schleiermacher's; and, though Irenaeus' account is not plausible in light of evolution, Schleiermacher's is. Advocates of a developmental account of the origins of sin have a genuine resource in Schleiermacher.